Digital Hospitality Paradox: Analyzing Food and Beverage Service VS. Mobile Or-Dering Star Hotel Staff Interactions : (Semawis – All Day Dinning X Hotel Semarang) - Aninda Wijayanti; Artin Bayu Mukti; Dita Aulia Rachma Nurul Farida (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The hospitality industry is experiencing rapid digital transformation, particularly with the widespread adoption of mobile ordering platforms in food and beverage services. This study seeks to examine how the use of a mobile ordering application affects staff–guest interactions at Semawis All-Day Dining, X Hotel Semarang. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation. The findings demonstrate that the integration of mobile ordering has significantly reshaped patterns of engagement between employees and guests, shifting from service approaches that emphasize relational warmth, friendliness, and emotional connection to those prioritizing efficiency, accuracy, and practicality. Although this system improves operational effectiveness, many employees feel that opportunities to establish deeper bonds with visitors are reduced, while senior staff frequently report experiencing technostress due to the pressure of adapting to new technologies. Consequently, the quality of personalized service and the traditional “human touch” in hospitality is gradually declining, even though efficiency levels have increased. To mitigate these challenges, hotels implement flexible strategies such as hybrid service models, combining technology-driven efficiency with face-to-face interaction to preserve the essence of hospitality. The research underscores the importance of considering relational, cultural, and psychosocial dimensions when implementing digital transformation in hotels. It concludes that successful integration of mobile ordering relies not only on operational convenience but also on strengthening technological literacy, providing continuous training, and adopting a human-centered service orientation. By balancing innovation with human values, hotels can maximize digital benefits while maintaining authentic hospitality experiences that remain memorable and meaningful for guests.